2009
DOI: 10.1007/s10344-009-0270-7
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia of free-ranging Northern chamois (Rupicapra rupicapra) with xylazine/ketamine and reversal with atipamezole

Abstract: One-hundred and fifty-five free-ranging Northern chamois (Rupicapra rupicapra) were anaesthetised in the course of a restocking programme using xylazine plus ketamine. Mean±SD dosages for xylazine and ketamine were 1.9±0.5 and 2.2±0.7 mg/kg, respectively. In 57 chamois, sedation was reversed using 0.3 ±0.1 mg/kg atipamezole. Although all the anaesthetic dosages tested immobilised free-ranging Northern chamois, shorter induction times (4.8±2.6 min), deeper sedation with no reaction to handling in >90% of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…An effect of age on induction time is often reported and is typically longer for adults (Jorgenson et al, 1990;Travaini et al, 1992;Dematteis et al, 2009). However, in our study, we observed the inverse relationship with juveniles showing a longer mean induction time.…”
Section: Discussionmentioning
confidence: 99%
“…An effect of age on induction time is often reported and is typically longer for adults (Jorgenson et al, 1990;Travaini et al, 1992;Dematteis et al, 2009). However, in our study, we observed the inverse relationship with juveniles showing a longer mean induction time.…”
Section: Discussionmentioning
confidence: 99%
“…Nussberger and Ingold (2006) showed that the behaviour of Alpine chamois is not affected by radio-collars. An injection of atipamezole was used to reverse the sedative effect (Dematteis et al 2009). The entire procedure usually took less than 40 min and was always performed with the assistance of a veterinarian.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…The sedative effect was reversed by an injection of atipamezole (Dematteis et al. ). The entire procedure usually took <40 min and was always performed with the assistance of a veterinarian.…”
Section: Methodsmentioning
confidence: 99%
“…Nussberger & Ingold (2006) showed that Alpine chamois behaviour is not affected by radio collars. The sedative effect was reversed by an injection of atipamezole (Dematteis et al 2009). The entire procedure usually took <40 min and was always performed with the assistance of a veterinarian.…”
Section: Study Site and Populationmentioning
confidence: 98%